Three steps to writing adaptive study protocols in the early phase clinical development of new medicines - Lorch, Ulrike (BioMed Central, 2014)
This article attempts to define terminology and to describe a process for writing adaptive, early phase study protocols which are transparent, self-intuitive and uniform. It provides a step by step guide, giving templates from projects which received regulatory authorisation and were successfully performed in the UK. During adaptive studies evolving data is used to modify the trial design and conduct within the protocol-defined remit. Adaptations within that remit are documented using non-substantial protocol amendments which do not require regulatory or ethical review. This concept is efficient in gathering relevant data in exploratory early phase studies, ethical and time- and cost-effective.